Multiportal subxiphoid thoracoscopic major pulmonary resections - Pfeuty, Karel; Lenot, Bernard (Journal of Thoracic Disease, 2019)
Background: New subxiphoid video-assisted thoracoscopic surgery (SVATS) approaches are emerging for major pulmonary resection. The underlying concept is to reduce invasiveness and morbidity, by minimising intercostal nerve trauma, without any concession on safety and carcinologic issues. This study describes and evaluates our initial experience in multiportal SVATS, compared to conventional VATS (CVATS). Methods: Between June 2016 and October 2017, 75 consecutive patients underwent major pulmonary resection with an original multiportal SVATS approach developed through a single or double access under the costal arch, unsystematically associated with intercostal ports for 5-mm instruments only. We retrospectively compared results of this SVATS group (n=75) against an historic CVATS group (n=75). Results: Fifty-one lobectomies, 20 segmentectomies and 4 pneumonectomies were achieved through multiportal SVATS. Sixty-eight malignant lesions and 7 benign lesions were noted. All patients with primary lung cancer underwent R0 resection and complete lymphadenectomy, with 11% of clinical N0 upstaging. When compared, the SVATS and CVATS groups were similar in terms of demographics and pathology. No statistical differences were observed in terms of conversion (9% vs. 12%), mean operative time (157 vs. 155 min), morbidity (24% vs. 32%) and 30-day mortality (0% vs. 1.3%). The SVATS group had a significantly shorter length of drainage (median: 1 vs. 3 days, P